Novel "all-in-one" sandwich technique for reconstruction of full-thickness defects of the lower eyelid: a case report. Issue 4 (April 2020) - Fodor, Lucian; Bran, Simion; Armencea, Gabriel; Onisor, Florin
The current paper presents a case report of lower eyelid reconstruction after removal of a basal cell carcinoma. Our novel reconstruction method consists of translation and rotation of a paramedian forehead flap into the defect, conjunctivorhinostomy for reconstruction of the nasolacrimal duct, and placement of a sandwich ear cartilage graft that is primarily seated into the forehead flap to maintain the vertical dimension of the eyelid. This "all-in-one" technique has the advantage of one-step reconstruction, avoiding multiple surgical procedures.